Status quo and challenges of rice production in sub-Saharan Africa - Saito, Kazuki; Senthilkumar, Kalimuthu; Dossou-Yovo, Elliott Ronald; Ali, I.; Johnson, J.M.; Mujawamariya, Gaudiose; Rodenburg, J. (Informa UK Limited, 2023)
Rice production in sub-Saharan Africa (SSA) has increaed ten-fold since 1961, whereas its consumption has exceeded the production and the regional self-sufficiency rate is only 48% in 2020. Increase in rice production has come mainly from increased harvested area. Yield increase has been limited and the current average yield in SSA is around 2 t ha−1. This paper aims to provide the status quo of (i) current rice production and its challenges, (ii) selected achievements in rice agronomy research mainly by the Africa Rice Center and its partners, and (iii) perspectives for future research on rice agronomy in SSA. The major problems confronting rice production include low yield in rainfed environments, accounting for 70% of the total rice harvested area. Rainfed rice yields are strongly affected by climate extremes such as water stresses, soil-related constraints, and sub-optimum natural resource management and crop management practices by smallholder farmers including poor water management, and suboptimal use of fertilizers, herbicides, and machineries. For alleviating these constraints, a wide range of technologies have been developed and introduced over the last three decades. These include water conservation technologies in rainfed and irrigated lowland rice, site-specific nutrient management practices, decision support tools such as crop growth simulation models, and labor-saving technologies. We conclude that further research efforts are needed to develop locally adapted agronomic solutions for sustainable intensification, especially in rainfed rice to enhance the resilience to climate change and increase land and labor productivity and sustainability of rice cultivation in SSA.